Processamento e propriedades do sistema ferroelétrico livre de chumbo (Bi, Na)TiO3 (Bi, K)TiO3 BaTiO3 - Quiroga, David Antonio Barbosa (Universidade Federal de São Carlos, 2015)
In this work, the lead-free ceramic powders of xBi0,5Na0,5TiO3 - (0,7186 - 0,7143x) Bi0,5K0,5TiO3 - (2814 - 2857x) BaTiO with x = 0,8200; 0,8625; 0,8792, 0,9126 and 0,9300 (BNBK1000x) were prepared by the solid state reaction method, followed by conventional densification. The ceramic bodies showed high density, which was higher than 95% in obtained samples. For the all ceramics were performed structural, micro structural, electric and anelastic characterizations. The X-ray diffraction (XRD) analysis indicated the formation of the complex perovskite type crystaline structure for all compositions analyzed without the presence of spurious phases. By the structural refinement by the Rietveld method of XRD data and by Raman spectroscopy were observed that for BNBK912 and BNBK930 compositions, at room temperature, the predominant symmetry is rhombohedral (R3c), while the BNBK820 composition exhibits a tetragonal crystalline symmetry (P4mm). For the BNBK879 and BNBK826 compositions presented a mixture of phases, possibly with rhombohedral and tetragonal symmetry, reaveling the morphotropic phase boundary (MPB) of this system. The microstructure of BNBK1000x ceramics was investigated by scanning electron microscopy (SEM), where the morphology grains with irregular sizes and shapes, where the increased levels of K+ and Ba2+ ions suppressed the growth of the grains. The characterizations by Raman spectroscopy at room temperature showed broad Raman modes, due to the chemical and/or structural disorder related to the substitution of elements Bi and Na for Ba and K. The ferroelectric characterizations at room temperature of the BNBK1000x ceramics showed that all compositions studied are ferroelectric. Through the comparison among the measurements of electrical impedance and mechanical spectroscopy, was possible to identify the different structural and electric phase transitions that were employed in the construction of a pseudodiagram of phases for the BNBK1000x compositions.
Keywords: Cerâmicas ferroelétricas; Contorno de fase morfotrópico; Anelasticidade; Transição de fase; Lead-free ferroelectrics ceramics; Morphotropic phase boundary (MPB); Ferroelectricity; Anelasticity; Perovskite structure; Phase transitions; CIENCIAS EXATAS E DA TERRA::FISICA